Emotional and Rational in the Decision to Use Payment Services of Islamic Financial Institutions for DIKTIS Students in Pamekasan Regency: The Mediating Effect of Regulation - Mubarak, Reza; Subairi; Faruq, Umarul; Fatoni, Ilhasul; Rohmatin, Atin (Faculty of Islamic Economics and Business, Madura Islamic State University, 2025)
There are many Islamic universities in Pamekasan regency, and their students can become ambassadors of sharia banking in society. At the same time, they also become a target market. However, not all students use sharia banking products. They use it because of the regulations from their campus. The aim of this research is to analyze whether Emotional and Rational influence students to make decisions on using Sharia Financial Institution Payment Services which are moderated by regulations at each university in Pamekasan Regency. This research uses respondents coming from active students at seven universities Directorate General of Islamic Higher Education (DIKTIS) in Pamekasan Regency. The data analysis used is multiple linear regression with moderator variables. Emotional Factors and Rational Factors as independent variables, Usage Decisions as dependent variables and Regulation as moderator variables. The results of this research are that emotional factors and rational factors affect the decisions of Pamekasan Regency DIKTIS students in using Sharia Financial Institution Payment Services. And Regulation as a moderator variable significantly strengthens the relationship between Rational Factors and Usage Decisions. Meanwhile, Emotional Factors cannot be strengthened in their relationship to Regulatory Use Decisions.